Pengaruh Kompetensi Pedagogik dan Motivasi Berprestasi Terhadap Kinerja Guru di SMPN 8 Sekayu Musi Banyuasin - Mujahidin, Mujahidin (BELAJEA: Jurnal Pendidikan Islam, 2016)
The objective of this research was to find out the effect of pedagogic competence and motivation toward teacherâs performance at SMPN 8 Sekayu in Musi Banyuasin Regency. Desctiptive qualitative study was used in this research. This research was done during three months. Subject of this research were 31 (thirty one) teachers Questionnaire was used to collect the data of this research. The data result of questionnaire were analyzed by using r test analysis, t test analysis, and F test analysis. Based on the r test analysis, the result showed that there was significance effect of pedagogic competence and motivation toward teacher performance. The value of R Square was 0.709, this value showed that the effect of pedagogic competence and motivation toward teacherâs performance (70.9 %). Based on the t test analysis, the result showed that there was significance effect of pedagogic competence toward teacherâs performance (t=0.02). The result also showed that there was significance effect of of motivation toward teacherâs performance (t=0.00). Meanwhile, the result of F test analysis (t=0,00) was there was a significance effect of pedagogic competence and motivation toward teacherâs performance. Keywords: Pedagogic Competence, Motivation, and Teacher Performance